A new replacement name for Allium denticulatum Brullo & Salmeri (Amaryllidaceae) - Zhang, Zhiyong; Idrees, Muhammad (Phytotaxa, 2023)
Allium Linnaeus (1753: 294) (Amaryllidaceae: Allioideae) is one of the largest monocot genera with more than 1063 species (Govaerts et al. 2023) and is naturally distributed throughout the northern hemisphere (Stearn 1992, Jiemei & Kamelin 2000, Fritsch & Friesen 2002). The major centers of diversity are located in southwestern and central Asia and the Mediterranean region (Choi & Oh 2011); a smaller center is in western North America (Friesen et al. 2006). Turkey has approximately 225 Allium taxa, classified into 15 sections, and one-third of these ones are endemic (Özhatay & Koçyiğit 2019). This genus is characterized by bulbs enclosed in membranous, fibrous or reticulate tunics, terminal umbel, free or basally connate, 1-veined tepals, often subgynobasic style, and loculicidal capsules with one or two seeds per loculus (Kollmann 1984, Fırat et al. 2018).